Tendências hidrológicas anuais e sazonais na bacia do rio Paraibuna, Parque Estadual da Serra do Mar (SP) / Annual and seasonal hydrological trends in Paraibuna river watershed, Serra do Mar State Park, São Paulo, Brazil - Mateus Ricardo Nogueira Vilanova (Sociedade & Natureza)
This article assesses the existence of monotonic trends in streamflow and rainfall series, in the stretch of Paraibuna River Watershed located in the region of Santa Virgínia and Cunha Centers, Serra do Mar Range State Park (SP). The Mann-Kendall test was applied to annual and seasonal series of the mentioned variables, in several intervals during the period of 1967 to 2011. Statistically significant negative trends were detected only in the long-term (from 1967) rainfall series, both annual and seasonal, from station 2344009, located in the region of Cunha. No significant trends were detected in the series of stations 2345067 (rainfall) and 58060000 (streamflow), located in Santa Virginia Center.